2021
DOI: 10.3389/fpubh.2021.704155
|View full text |Cite
|
Sign up to set email alerts
|

Does the Economic Growth Improve Public Health? A Cross-Regional Heterogeneous Study in China

Abstract: On public health, the effect of economic growth in China is analyzed in this paper by using the panel threshold regression model. The empirical study from 2000 to 2017 shows that China's economic growth has a significant threshold effect on public health. After the threshold is exceeded, public health will be improved dramatically. The threshold effect is heterogeneous at the regional level. The eastern region has no threshold, and both central and western regions have a single significant threshold. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 52 publications
(69 reference statements)
3
33
1
1
Order By: Relevance
“…However, carbon emission is significantly and positively related to life expectancy showing that carbon emission enhances life expectancy. This result contrasts with many previous studies ( 17 , 29 , 30 ). One possible explanation of this positive association is improvement in overall health is explained by Gangadharan and Valenzuela ( 52 ), who assert that healthcare gains cancel the environmental losses due to improvement in income level.…”
Section: Resultscontrasting
confidence: 99%
See 3 more Smart Citations
“…However, carbon emission is significantly and positively related to life expectancy showing that carbon emission enhances life expectancy. This result contrasts with many previous studies ( 17 , 29 , 30 ). One possible explanation of this positive association is improvement in overall health is explained by Gangadharan and Valenzuela ( 52 ), who assert that healthcare gains cancel the environmental losses due to improvement in income level.…”
Section: Resultscontrasting
confidence: 99%
“…This leads to a high mortality rate. The result regarding the economic growth and life expectancy is consistent with the findings of Niu et al ( 17 ). This positive association is due to prioritizing the improvement in the healthcare sector in GCC countries.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Therefore, governments, enterprises, the public, and NGOs have achieved comprehensive interactive and cooperative governance. As an innovative governance model used to solve governance dilemmas of complex public affairs and to meet the needs of regional coordinated development, governments around the world have actively explored and formed a series of distinctive new governance practices in environmental governance [ 33 ], economic development [ 34 ], traffic management [ 35 ], energy management [ 36 ], waste management [ 37 ], public health [ 38 ], and other fields. It can be concluded that cross-regional governance has become an effective governance model used to solve cross-regional public affairs and to realize regional sustainable development.…”
Section: Literature Reviewmentioning
confidence: 99%